1998
DOI: 10.1111/j.1540-8167.1998.tb00954.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Ventricular Fibrillation by Transvenous Defibrillating Leads:

Abstract: There are only minor differences in detection/redetection of ventricular fibrillation between dedicated and integrated (with tip to coil spacing of 18.3 mm) recording configurations. Detection times during ventricular fibrillation are related to the signal variance or energy recorded. Differences in the sensing performance of the two recording configurations can be explained by the differences in signal energy between the dedicated and integrated recordings that occur during ventricular fibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Our results are consistent with past investigations. An older study 11 did not find significant differences between the sensed bipolar and integrated bipolar electrograms with an earlier type of lead.…”
Section: Discussionmentioning
confidence: 69%
“…Our results are consistent with past investigations. An older study 11 did not find significant differences between the sensed bipolar and integrated bipolar electrograms with an earlier type of lead.…”
Section: Discussionmentioning
confidence: 69%
“…Differences in the sensing performance of true and integrated bipolar leads have been reported in the literature [4] [5] [6] [13]. The cause of this discrepancy has not been clearly elucidated.…”
Section: Discussionmentioning
confidence: 93%
“…In redetection, for example, it has been postulated that the more likely explanation is myocardial stunning occurring with an integrated bipolar configuration [5]. On the other hand, some authors concentrate on the measurement properties of the lead system, and argue that the quality of the signals recorded by true and integrated bipolar configurations is different [4] [6] [13].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors concentrate on the measurement properties of the lead system and argue that the quality of the signals recorded by dedicated and integrated bipolar configurations is different. [12][13][14] Requena-Carrión et al 15 reported that EGM features can be explained by estimating the extent of myocardium within the range of the lead. They investigated differences in the sensing range of true and integrated bipolar leads by means of bioelectric signal modeling and numeric methods reporting that dedicated bipolar leads have a narrower antenna/sensing field/range than integrated bipolar leads.…”
Section: Discussionmentioning
confidence: 99%